2021
DOI: 10.12739/nwsa.2021.16.1.4b0037
|View full text |Cite
|
Sign up to set email alerts
|

Yeti̇şki̇nlerde Beslenme Okuryazarliğin Sağlikli Beslenmeye İli̇şki̇n Tutumlar Ve Beden Kütle İndeksi̇ İle İli̇şki̇si̇

Abstract: YETİŞKİNLERDE BESLENME OKURYAZARLIĞIN SAĞLIKLI BESLENMEYE İLİŞKİN TUTUMLAR VE BEDEN KÜTLE İNDEKSİ İLE İLİŞKİSİ ÖZ Bu çalışmada yetişkinlerde beslenme okuryazarlığı düzeyini tespit etmek ve bunun, sağlıklı beslenmeye ilişkin tutumlar ve Beden Kütle İndeksi (BKİ) ile ilişkisinin araştırılması amaçlanmıştır. Kesitsel ve tanımlayıcı nitelikte olan bu çalışmaya Türkiye'de yaşayan 20-65 yaş arası 750 gönüllü dahil edilmiştir. Veri toplama aracı olarak; Sosyodemografik bilgi formu, Yetişkinlerde Beslenme Okuryazarlığ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 3 publications
0
7
1
6
Order By: Relevance
“…Unlike the findings of this study, Aliye Özenoğlu et al [21] found that men show a higher attitude towards healthy nutrition than women. Gençalp [22] reported that there is no significant difference in the gender variable in the participation of university students in nutrition and physical activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the findings of this study, Aliye Özenoğlu et al [21] found that men show a higher attitude towards healthy nutrition than women. Gençalp [22] reported that there is no significant difference in the gender variable in the participation of university students in nutrition and physical activity.…”
Section: Discussioncontrasting
confidence: 99%
“…There are also studies reporting different findings when the literature is examined [19,21]. Buhaş et al [33] said that a healthy lifestyle can be related not only to the physical body but also to the mental state.…”
Section: Discussionmentioning
confidence: 99%
“…Özenoğlu, Gün, Karadeniz et al [20], when the socio-demographic characteristics of the participants were compared with the total scores of their attitudes towards healthy eating, no significant difference was found between gender and education level.…”
Section: Discussionmentioning
confidence: 95%
“…Yetişkin bireyler ile yapılan bir çalışmada, bireylerin yüksek düzeyde sağlıklı beslenmeye ilişkin tutuma sahip olduğu ve yaş ile sağlıklı beslenmeye ilişkin tutumlar arasında bizim çalışmamıza paralel şekilde pozitif yönde ilişki olduğu saptanmıştır. 19 Yine yetişkin bireyler ile yapılan başka bir çalışmada da, yaş arttıkça bireylerin daha fazla sağlıklı beslenmeye ilişkin tutuma sahip olduğu belirlenmiştir. 20 Obezite önyargısı ve obez bireylere karşı olumsuz tutumlar sağlık alanında çeşitli meslek gruplarında bildirilmektedir.…”
Section: Discussionunclassified